The development of geographic information system (GIS) for the elctricity distribution network of SONELGAZ - Boukhalat, Abderrahim (FACULTE Mathématique et Informatique DEPARTEMENT D’ Informatique, 2018)
Sonelgaz, the National Society for Electricity and Gas is a state-owned utility in charge of electricity and natural gaz and production, transportation and distribution in Algeria. SDE M’sila is the agency for distributing and carrying electricity and gaz from transformation systems to individual consumers in the state of M’sila. For electric power distribution, the power is transmitted over a large network, in which, the power is transformed from primary lines of medium voltage to lower voltage for end-users using transformers. The electricity distribution network of M’sila is wide network that consists of 20 primary lines of medium voltage called Departs, that are branching out over the region of M’sila resulting in more than 5000 transformers, which makes the control and management of this complex network so challenging task. In this dissertation, we aim to build a geographical information systems (GIS) to facilitate the control and management of this network. We employ so many geographical techniques including but not limited to: geodatabase, geospatial projection, geometry processing and graphic representation, in order to help Sonelgaz engineers as well as high responsibles to get unified and representative vision on the entire network, thus, they can get enhance the network, and take the appropriate decisions.
Keywords: Electricity, GIS, Geospatial, Distribution, Geodatabase, ArcGIS.